A bibliometric analysis of microbial forensics from 1984 to 2022: progress and research trends - Guo, Xiangnan; Gu, Liya; Luo, Yue; Wang, Shuangshuang; Luo, Haibo; Song, Feng (Frontiers in Microbiology, 2023)
Microbial forensic is a rapidly evolving discipline that has gained significant momentum in recent years. The paper evaluated relevant results over the last four decades from 1984 to 2022 all over the world, aiming to analyze the growing trends and research orientations of microbial forensic. Using “microbial forensic” as the search topic in Web of Science Core Collection, the systematic retrieval identified 579 documents relevant to the field and draw many statistical tables and maps to make the retrieval results visible. According to further bibliometric analysis, there are increasing number of publications related to microbial forensic from the overall trend, with the highest number of publications recorded in 2021. In terms of the total number of articles, the USA and China were both the leading contributors to the field among 40 counties. The field has developed rapidly in recent years based on the development of next-generation sequencing. Over the course of its development, there are rich keywords in the research of scholars, which focus on diversity and identification. What’s more, despite the early hot topic being PCR (the use of PCR to probe microorganisms), in recent years, the topics, markers and the potential application of microorganisms in forensic practice have become hot, which also indicates the future research directions of microbial forensic.